Effect of zinc management practices on growth, yield and biofortification of upland rice genotypes under Eastern Himalayas ecologies - Akshay Kumar Yogi; Ram Swaroop Bana; Shanti Devi Bamboriya (Annals of Agricultural Research, 2023)
A field study was conducted at ICAR Research Complex for North Eastern Hill Region, Umiam, Meghalaya, during kharif season of 2018-19 to evaluate the effect of three genotypes of upland rice and Zn application protocols on rice growth, yield attributes, yield and grain Zn content under Eastern Himalayan ecologies. The experiment was conducted in split plot design allotting three advance genotypes of rice (Bhalum 1, Bhalum 3 and Bhalum 5) in main plots and four Zn application protocols [control; soil application of Zn @ 2.5 kg ha-1(basal)+ Zn solubilizing bacteria; soil application of Zn @ 5 kg ha-1(basal) and foliar Zn application at panicle initiation and flowering stages @ 0.5 %] in sub plots. The result revealed that Bhalum 3 genotype of rice performed well over Bhalum 1 and Bhalum 5 in terms of growth, yield parameters and yield (2.89 t ha-1). Foliar Zn application significantly improved the growth and yield parameters and grain yield (3.14 t ha-1) of upland rice. Moreover, Zn foliar application during panicle initiation and maximum flowering were shown to be promising protocol enabling Zn biofortification in rice grain (34 mg kg-1) over control (24 mg kg1 ). This study suggests that dual spray of zinc sulphate (0.5%) at panicle initiation and flowering stages on upland rice can improve yield and Zn content over no Zn application in Northern Eastern Himalayan Region.